UPAYA MENGATASI RASA TIDAK PERCAYA DIRI DENGAN PENDEKATAN SOLUTION FOCUSED THERAPY PADA SISWA SMP DI KAMPUNG NGAGLIK RT05 RW12 MOJOSONGO, WONOWOSO, JEBRES, SURAKARTA TAHUN PELAJARAN 2020/2021. - Damayanti, Elfadani (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
The purpose of this research is to overcome the lack of confidence in junior high school students in Kampung Ngaglik RT05 RW12 Mojosongo, Wonowoso, Jebres, Surakarta in daily activities. This study was conducted at Kampung Ngaglik RT05 RW12 Mojosongo, Wonowoso, Jebres, Surakarta. The research method used is the PTBK method. In this study using the PTBK approach consisting of 2 cycles and each cycle consists of 4 main activities with name : planning, action, observation and reflection. The data collection techniques used in this study are observation, interviews and documentation. From the results of this study found that the change in behavior from not confident to confident in junior high school students in Pre-Cycle obtained results (40%) then from Pre Cycle to Cycle I increased by (65%) which is categorized as moderate. Furthermore, in Cycle II obtained (85%) which is categorized very well. Thus it can be concluded that from Pre-Cycle to Cycle I then to Cycle II shows a change from bad to good and to very good. Keywords : Overcoming Self-Confidence, Solution Focused Therapy Approach